Protective potential of structural proteins of the SARS-CoV-2 virus in protecting against COVID-19 - Inna V. Dolzhikova; Daria M. Grousova; Ilya D. Zorkov; Anna A. Ilyukhina; Anna V. Kovyrshina; Olga V. Zubkova; Olga D. Popova; Tatiana A. Ozharovskaya; Denis I. Zrelkin; Daria M. Savina; Ekaterina G. Samokhvalova; Amir I. Tukhvatulin; et al. (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Many different vaccines for the prevention of COVID-19 have received emergency use approval in the shortest possible time. Due to the high rate of variability of the pathogen, in this study we analyzed the variability of the structural proteins of the SARS-CoV-2 virus and compared their protective potential in protecting animals from COVID-19.